Targeting of chimeric antigen receptor T cell metabolism to improve therapeutic outcomes - Nanjireddy, Priyanka Maridhi; Olejniczak, Scott H.; Buxbaum, Nataliya Prokopenko (Frontiers in Immunology, 2023)
Genetically engineered chimeric antigen receptor (CAR) T cells can cure patients with cancers that are refractory to standard therapeutic approaches. To date, adoptive cell therapies have been less effective against solid tumors, largely due to impaired homing and function of immune cells within the immunosuppressive tumor microenvironment (TME). Cellular metabolism plays a key role in T cell function and survival and is amenable to manipulation. This manuscript provides an overview of known aspects of CAR T metabolism and describes potential approaches to manipulate metabolic features of CAR T to yield better anti-tumor responses. Distinct T cell phenotypes that are linked to cellular metabolism profiles are associated with improved anti-tumor responses. Several steps within the CAR T manufacture process are amenable to interventions that can generate and maintain favorable intracellular metabolism phenotypes. For example, co-stimulatory signaling is executed through metabolic rewiring. Use of metabolic regulators during CAR T expansion or systemically in the patient following adoptive transfer are described as potential approaches to generate and maintain metabolic states that can confer improved in vivo T cell function and persistence. Cytokine and nutrient selection during the expansion process can be tailored to yield CAR T products with more favorable metabolic features. In summary, improved understanding of CAR T cellular metabolism and its manipulations have the potential to guide the development of more effective adoptive cell therapies.